Analysis of bicyling trends and policies in large North American cities: Lessons for New York. Final Report. - Pucher, John; Buehler, Ralph (My University, 2011)
This research report reviews trends in cycling levels, safety, and policies in large North American cities over the past two decades. Aggregate national data as well as city-specific case study data for nine large cities (Chicago, Minneapolis, Montréal, New York, Portland, San Francisco, Toronto, Vancouver, and Washington) have been analysed. The number of bike commuters in the USA rose by 64% from 1990 to 2009, and the bike share commuters rose from 0.4% to 0.6%. Over the shorter period from 1996 to 2006, the number of bike commuters in Canada rose by 42%, and the bike share of commuters rose from 1.1% to 1.3% in the USA. From 1988 to 2008, cycling fatalities fell by 66% in Canada and by 21% in the USA. Cycling rates have risen much faster in the nine case study cities than in their countries as a whole, at least doubling in all the cities since 1990. The case study cities have implemented a wide range of infrastructure and programs to promote cycling and increase cycling safety.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Stadtverkehr; Statistik; Fallstudie; Fahrradförderung; Fahrradinfrastruktur; Fahrradnutzung; Auswertung; Trendanalyse